Interaction of isoflavonoids with human liver microsomal cytochromes P450: inhibition of CYP enzyme activities - Kopečná-Zapletalová, Michaela; Krasulová, Kristýna; Anzenbacher, Pavel; Hodek, Petr; Anzenbacherová, Eva (Xenobiotica, 2017)
1. The possibility of interaction of isoflavonoids with concomitantly taken drugs to determined isoflavonoids safety was studied. Inhibition of nine forms of cytochrome P450 (CYP3A4, CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2C9, CYP2D6 and CYP2E1) by 12 isoflavonoids (daidzein, genistein, biochanin A, formononetin, glycitein, equol and six glucosides, daidzin, puerarin, genistin, sissotrin, ononin and glycitin) was studied systematically. 2. The most potent inhibitors were genistein and daidzein inhibiting noncompetitively the CYP2C9 with Ki of 35.95 ± 6.96 and 60.56 ± 3.53 μmol/l and CYP3A4 (inhibited by genistein with Ki of 23.25 ± 5.85 μmol/l also by a noncompetitive mechanism). Potent inhibition of CYP3A4 was observed also with biochanin A (Ki of 57.69 ± 2.36 μmol/l) and equol (Ki of 38.47 ± 2.32 μmol/l). 3. Genistein and daidzein inhibit noncompetitively CYP3A4 and CYP2C9. With plasma levels in micromolar range, a clinically important interaction with concomitantly taken drugs does not seem to be probable.
Keywords: jaterní mikrozomy; Liver; Humans; Cytochrome P-450 CYP2C19; lidé; Glucosides; cytochrom P-450 CYP1A2; Isoflavones; Cytochrome P-450 CYP1A2; lékové interakce; játra; Microsomes, Liver; isoflavony; Drug Interactions; Cytochrome P-450 Enzyme System; systém (enzymů) cytochromů P-450; glukosidy; cytochrom P450 CYP2C19